Genetic Variability and Correlation Studies for Seed Morphology, Seedling Growth and Biochemical Traits in Neem (Azadirachta indica A. Juss) - Kaushik, N.; Kaushik, J. C.; Nautiyall, S. (Indian Forester, 2012)
Genetic parameters in seed morphology, germination, seedling growth and biochemical contents of seed traits in Azadirachta indica collected from different parts of Haryana, India were assessed. The 'F' values for all the characters studied were significant (P<0.05), indicating the presence of ample genetic variation for all characters. The estimated coefficient of variance ranged from 1.93 to 8.73 per cent. The genetic advance, as percentage of means ranged from 21.29 per cent for seed breadth to 88.27 per cent for root length. The other characters viz. collar diameter (73.56 %) and shoot length also showed high values for genetic advance as percentage of mean High heritability (99.00%) and genetic gain were recorded for 100-seed weight, seed germination, shoot length, palmitic acid and stearic acid indicating the additive gene action. Seed size (length and breadth) and 100-seed weight was significantly and positively correlated with oil content, positively correlated with azadirachtin content, palmitic acid and oleic acid, however negatively correlated with steric acid and myrstic acid. Considering seed morphology, germination, azairachtin content and quantitative and qualitative characters of oil, the best performing plus trees were,T6 (Kurukshetra) of the Karnal , T6 (Pinjore II) from Panchkula, (T6) from Premnagar of Bhiwani and tree (T4) from Jhatipur of Sonipat provenance.